Combining Confocal Laser Scanning Microscopy with Serial Section Reconstruction in the Study of Adult Neurogenesis - Luzzati, Federico; Fasolo, Aldo; Peretto, Paolo (Frontiers in Neuroscience, 2011)
Current advances in imaging techniques have extended the possibility of visualizing small structures within large volumes of both fixed and live specimens without sectioning. These techniques have contributed valuable information to study neuronal plasticity in the adult brain. However, technical limits still hamper the use of these approaches to investigate neurogenic regions located far from the ventricular surface such as parenchymal neurogenic niches, or the scattered neuroblasts induced by brain lesions. Here, we present a method to combine confocal laser scanning microscopy (CLSM) and serial section reconstruction in order to reconstruct large volumes of brain tissue at cellular resolution. In this method a series of thick sections are imaged with CLSM and the resulting stacks of images are registered and 3D reconstructed. This approach is based on existing freeware software and can be performed on ordinary laboratory personal computers (PC). By using this technique we have investigated the morphology and spatial organization of a group of doublecortin (DCX)+ neuroblasts located in the lateral striatum of the late post-natal guinea pig. The 3D study unravelled a complex network of long and poorly ramified cell processes, often fascicled and mostly oriented along the internal capsule fibre bundles. These data support CLSM serial section reconstruction as a reliable alternative to the whole mount approaches to analyze cyto-architectural features of adult germinative niches.